Miliary tuberculosis with unusual matted giant mesenteric lymph nodes - Parnpen Viriyavejakul (2018)
We report a case of miliary tuberculosis in a 10-month old female with unusual matted giant mesenteric lymph nodes. She presented with prolonged fever and poor feeding for two months. With the evidence of miliary pattern in chest X-ray and the positive acid-fast bacilli from the sputum, she was treated with antituberculous chemotherapy. She died from pneumomediastinum and pneumopericardium. Postmortem findings disclosed miliary tuberculosis involving major organs. Acid-fast bacilli were numerous. Large matted mesenteric lymph nodes measuring 10 × 6 × 5 cm3 were noted. A strikingly large palpable matted mesenteric lymph nodes in suspected miliary tuberculosis should not be confused with tumors in the children.